(untitled) (The Research of Medical Science Review, 2024)
Chronic neck pain and dyskinesia are debilitating conditions that significantly affect individuals' functional capacity and quality of life. Scapular stability training may offer a promising therapeutic approach to alleviate pain, enhance motor control, and induce neuroplastic changes in individuals suffering from these conditions. This study explores the effects of scapular stability training on neuroplastic adaptations in the motor cortex and functional improvements in individuals with chronic neck pain and dyskinesia. Thirty participants were randomly assigned to either a scapular stability intervention group or a control group. The intervention, which consisted of a 6-week regimen focused on strengthening and stabilizing the scapular muscles, was assessed using a variety of outcome measures, including pain intensity (Visual Analog Scale), neck disability (Neck Disability Index), scapular kinematics, and neuroplastic changes measured through fMRI. The results revealed significant improvements in pain reduction, disability, and scapular movement patterns in the intervention group, alongside neuroplastic changes in the motor cortex. These findings underscore the potential of scapular stability training not only to reduce symptoms of chronic neck pain but also to promote beneficial neural adaptations, supporting its inclusion as a viable treatment option for chronic neck pain and dyskinesia. Future studies should explore the long-term effects and refined protocols for scapular stability training to maximize its therapeutic potential.